2020
DOI: 10.1038/s41598-020-70334-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the accessible chromatin, transcriptome and Ascl1-binding correlate with the loss in Müller Glial regenerative potential

Abstract: Diseases and damage to the retina lead to losses in retinal neurons and eventual visual impairment. Although the mammalian retina has no inherent regenerative capabilities, fish have robust regeneration from Müller glia (MG). Recently, we have shown that driving expression of Ascl1 in adult mouse MG stimulates neural regeneration. the regeneration observed in the mouse is limited in the variety of neurons that can be derived from MG; Ascl1-expressing MG primarily generate bipolar cells. To better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…After retinal damage in zebrafish, miR-216a is downregulated allowing increased expression of Dot1l which leads to activation of Wnt target genes, presumably by altering chromatin accessibility surrounding these genes (Kara et al, 2019 ). The idea that dedifferentiation of MG involves changes in chromatin accessibility is expected and has been experimentally supported (Jorstad et al, 2017 ; Mitra et al, 2018 ; VandenBosch et al, 2020 ). When combined with Ascl1 overexpression in an NMDA damage model in adult mice, the addition of the general histone deactylase inhibitor trichostatin A (TSA) stimulated neuronal regeneration which was otherwise only observed in developing mice <12 days old (Jorstad et al, 2017 ).…”
Section: Mir-216a/dot1lmentioning
confidence: 96%
See 1 more Smart Citation
“…After retinal damage in zebrafish, miR-216a is downregulated allowing increased expression of Dot1l which leads to activation of Wnt target genes, presumably by altering chromatin accessibility surrounding these genes (Kara et al, 2019 ). The idea that dedifferentiation of MG involves changes in chromatin accessibility is expected and has been experimentally supported (Jorstad et al, 2017 ; Mitra et al, 2018 ; VandenBosch et al, 2020 ). When combined with Ascl1 overexpression in an NMDA damage model in adult mice, the addition of the general histone deactylase inhibitor trichostatin A (TSA) stimulated neuronal regeneration which was otherwise only observed in developing mice <12 days old (Jorstad et al, 2017 ).…”
Section: Mir-216a/dot1lmentioning
confidence: 96%
“…One goal for these studies is to determine the factors and pathways that allow for persistent and spontaneous regeneration. Focusing on the retina, knowledge gained from zebrafish studies (Wan and Goldman, 2016 ; Yao et al, 2018 ; Hoang et al, 2020 ; VandenBosch et al, 2020 ; Zhou et al, 2020 ) can be applied to identify common mechanisms that induce mammalian retina regeneration. Here, we will focus on the explicit role of miRNAs during MG reprogramming.…”
Section: Introductionmentioning
confidence: 99%
“…In mice the forced ectopic expression of the bHLH transcription factor, Ascl1, when combined with cell death is sufficient to stimulate a Müller glia to enter the cell cycle [ 103 ]. The efficiency of this response is enhanced when the expression of Ascl1 and retinal injury are combined with a treatment of the histone deacetylase inhibitor, trichostatin-A (TSA), indicating that chromosome structure in mammalian Müller glia may limit the regenerative capacity of these cells [ 104 , 105 ]. These results point toward common molecular mechanisms for reprogramming Müller glia in all vertebrates.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…One member of the group compensates for the loss of another and shares the same binding motif (46). bHLH transcription factors, such as Atoh7 and Ascl1, which are expressed in RPCs, bind to the same E-box motif as Atoh1 (the CAGCTG motif) (47,48), suggesting that these transcription factors may cooperate with Meis1/2. Only half of Meis1/2-bound regulatory regions in the retina contained the Meis motif, which indicated that Meis1/2 must bind DNA through noncanonical motifs in cooperation with other transcription factors.…”
Section: Meis1 and Meis2 Regulate The Rpc-specific Genes In Cooperation Withmentioning
confidence: 99%